О роли извержения вулкана Мерапи в аномальном понижении ОСО над Томском в апреле 2011 г. - Зуев В. В. Владимир Владимирович; Зуева Н. Е. Нина Евгеньевна; Савельева Е. С.; Баженов О. Е.; Невзоров А. В. Алексей Викторович (2015, 2015)
Заглавие с экрана